Comparative investigation of the effect of Ukrain on growth of ascite and solid forms of ehrlich’s carcinoma - Susak, Ya.M.; Skivka, L.M.; Rudik, M.P.; Pozur, V.V.; Liubunya, A.V. (Experimental Oncology, 2010)
Ukrain (NSC-631570) is a cytostatic and immunomodulating semisynthetic compound of thiophosphate-modified alkaloids of Chelidonium majus L. It has selective cytotoxicity against cancer cells without healthy cells damaging. Dosage range, methods of introduction and duration of administration of the drug vary. Aim: To carry out comparative investigation of effect of Ukrain on growth of different form of Ehrlich’s carcinoma. Methods: Ehrlich’s carcinoma cells were transplanted intraperitoneally and subcutaneously between the scapulas. Ukrain was administered intraperitoneally for 6 days (0.25 mg per mice of 20 g, it’s 0.1 LD50). The effect of drug on tumor growth was evaluated by the indexes of tumor growth inhibition (in the case of solid form), total number of tumor cells in ascites, number of viable tumor cells (in the case of ascitic form) and average life span of experimental animals. Cell cycle distribution of cancer cells was determined by flow cytometry. The number of circulating phag ocytes was determined by flow cytometry with use of FITC-labelled S. aureus Cowan. Results: Intraperitoneal Ukrain administration in mice with ascite form of Ehrlich’s carcinoma resulted in moderate tumor growth retardation, but was accompanied by acute local inflammation and caused reduction of life span of experimental animals. In mice bearing solid form of Ehrlich’s carcinoma treatment with Ukrain led to significant tumor growth inhibition and slight increase of life span. In mice bearing both of tumor variants treatment with drug caused restitution of the number of circulating phagocytes in peripheral blood, more expressed in mice bearing ascite tumor variant. Conclusion:Thus, anticancer activity of the Ukrain is more expressed in the case of solid variant of Ehrlich’s carcinoma. This effect is mediated by direct apoptotic action of drug on Ehrlich’s carcinoma cells and positive immunomodulating effect on tumor-bearing organism.